DEICTIC MITIGATION VS COMMISSIVE ACTS IN POLITICAL INTERVIEW (BASED ON THE MODERN EUROPEAN DISCOURSE OF AID TO UKRAINE) - Nataliia K. Kravchenko; Sviatoslav I. Vylinskyi; Oleksandr I. Yudenko (Вісник університету ім. А. Нобеля. Серія Філологічні науки)
The article deals with the problem of correlation between the illocutionary force of indirect commissive acts and shields as deictic mitigating markers that reduce the level of promises by influencing their felicity conditions. The purpose of the article is to clarify the types of deictic shields and their function in weakening the illocutionary force of indirect promises in the European political discourse of assistance to Ukraine. The purpose is achieved by solving the following objectives that determine the research algorithm, including (a) felicity conditions revealing for commissives, weakened by shields that affect the illocutionary force of acts; (b) identifying those deictic coordinates of statements, the reference to which weakens the illocutionary force of commissives; (c) lexical-semantic and syntactic deictic mitigators complex determination. To achieve the purpose and objectives set in the article, the following research methods are used: the method of speech acts analysis and the method of inferencing the shields-based conventional implicatures, supplemented by elements of componential analysis. The article reached the following principal results. Firstly, among the felicity conditions for commissives weakened by shields, the article highlights the condition of speaker’s sincerity and the preparatory condition of his / her ability to perform a promissive act. Due to the shields, the promise is transferred from the scope of the action to the scope of the speaker’s possibilities. Secondly, based on the understanding of shields as the markers affecting either the speaker’s / addresser’s face-protecting attitude to the proposition or the deictic space-temporal-object coordinates of the utterance, the paper has identified that the illocutionary force of indirect commissives is mitigated by personal, temporal and object shields. Thirdly, we have singled out and specified a set of illocution-mitigating deictic devices, including means of role-playing deixis, epistemological modal verbs and their substitutes, which denote or connotate semes of “capabilities” and “possibilities”, means of negation, temporary deixis devices, i.e. the lexical and grammatical markers of future tense, resulting in the vagueness of promises / obligations; presuppositional adverbs with inference pattern of “impediment to a promised action”; passive structures that withdraw the speaker from the position of phrasal subject and an agent of the promising action; verbs and adverbs, which in their inference patterns contain the denotative or contextually connotated semes of a temporal reference to an indefinite future; metonymic generalization of the agent of action. The prospect for further research is the analysis of all types of mitigators, including bushes, hedges and shields, in their projection on rhetorical and manipulative methods of argumentation in political discourse as manifested by the discourse-forming concept “Caution”.